ANALYZING THE SELECTION OF PARACETAMOL PREPARATIONS AVAILABLE IN THE UKRAINIAN PHARMACEUTICAL MARKET - Драчук, Віра; Заморський, Ігор; Щудрова, Тетяна; Копчук, Тамара; Горошко, Олександра; Дикал, Мар'яна (SWorldJournal, 2023)
The article presents the results of a comprehensive marketing analysis of the structure of the domestic pharmaceutical market of the assortment of drugs with the active ingredient paracetamol by producing countries and the variety of dosage forms. Taking